A Shock to the System: HIV among Older African Women in Zimbabwe - Ndakaitei Chikonzo; Asta Rau; Jan K. Coetzee; Anne Ryen; Florian Elliker; Amanda Young-Hauser (Qualitative Sociology Review, 2018)
HIV remains a threat to the ordinary everyday life of older woman in African society. In what can be called “a reality shock,” HIV challenges most of the ordinary everyday endeavors in conservative African societies as it imposes new Western prevention, treatment, and health-management methods over long-held African traditions. The reality of the “Western” HIV epidemic, and its impact on the “African” ordinary everyday life, demands that the infected undergo a paradigm shift in order for them to live harmoniously within their society. This calls for a re-examination of traditional values and a strong sense of responsibility, courage, and determination to remain relevant and not be considered odd in one’s community, especially as one grows old with the virus. The study, which focuses on the experiences of women from the Manicaland Province in Zimbabwe who are aging with HIV, observes that growing old with an HIV infection fosters forms of inner strength and wisdom that enable the infected to disregard some of the unquestioned traditions and employ effective ways of living well with the life-threatening condition.